MODUL PROJEK PROFIL PELAJAR PANCASILA TEMA KEWIRAUSAHAAN UNTUK PESERTA DIDIK SEKOLAH DASAR - Pamungkas, Katya Osylany; Nur Ngazizah; Arum Ratnaningsih (Universitas Pendidikan Ganesha, 2023)
Many teachers still need help developing appropriate project modules, resulting in students' lack of understanding. This research aims to develop a Pancasila Student Profile Project Module with the Entrepreneurship Theme. This type of research is development research using the ADDIE model. This research involved 28 students consisting of 15 male and 13 female students. The development of material, media, and practitioner experts validated this project's methods using observation, interviews, questionnaires, documentation and tests. The instrument used was a questionnaire. Data analysis techniques use qualitative and quantitative analysis. Test effectiveness using N-gain. The research results are that the Pancasila student profile project module with the theme of entrepreneurship meets the criteria for validity, practicality and effectiveness. This project module is valid because it meets the content, language and presentation criteria. Validation of the feasibility of the Pancasila student profile project module by media experts, namely 97.5%, practitioner experts got a percentage of 97.4% and material experts a percentage of 99.3%. In the practical aspect, the percentage was 84.2% for limited trials and 85.8% for extensive trials. In the effectiveness aspect, the N-gain results show the effective category. Educators can use the project module to develop the entrepreneurial skills of fourth-grade elementary school students.